SPE/IADC Drilling Conference 2003
DOI: 10.2118/79856-ms
|View full text |Cite
|
Sign up to set email alerts
|

Cuttings Transport with Foam in Horizontal & Highly-Inclined Wellbores

Abstract: fax 01-972-952-9435. AbstractFoams are of considerable interest for annular pressure management in many drilling applications. While foam rheology and hydraulics have been studied in the past, knowledge of cuttings transport with foam is very limited for vertical wells, and even less well understood for horizontal and inclined-well configurations. In this paper, cuttings transport with foam in horizontal and highly-inclined wells is analyzed.Using the principles of mass and linear momentum conservation, a mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 8 publications
0
32
0
1
Order By: Relevance
“…Fig. 12 shows the comparison between the simulator prediction and experimental results from this and previous studies (Duan, 2007;Chen, 2005;Ozbayoglu, 2002). The simulator gives reasonable predictions compared to the experimental measurements within the range of these investigations.…”
Section: Computer Simulation Results Comparisonmentioning
confidence: 54%
See 2 more Smart Citations
“…Fig. 12 shows the comparison between the simulator prediction and experimental results from this and previous studies (Duan, 2007;Chen, 2005;Ozbayoglu, 2002). The simulator gives reasonable predictions compared to the experimental measurements within the range of these investigations.…”
Section: Computer Simulation Results Comparisonmentioning
confidence: 54%
“…A Cuttings Transport Simulator was developed based on the experimental results from this study and previous studies, and the modeling approaches are inherited from the work conducted by Duan (2007) and Ozbayoglu (2002). The simulator is capable of predicting cuttings concen- tration, cuttings bed height, frictional pressure loss gradient and foam in situ velocity by taking the input of wellbore geometry, gas and liquid flow rate, pressure, temperature, ROP, drill pipe rotation speed and wellbore inclination angle.…”
Section: Computer Simulation Results Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of recent studies (Hansen et al, 1999;Nouri et al, 1993;Nouri and Whitelaw, 1997;Wang et al, 2000;Ozbayoglu, 2002;and Silva and Shah, 2000) conducted on Newtonian and nonNewtonian fluids experimentally evaluated the reduction of frictional pressure loss due to eccentricity. Results confirmed frictional pressure loss reduction of up to 40% due to eccentricity.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Ozbayoglu et al 20 concluded that there is no "best" model to explain the rheological behavior of foam for all quality ranges. However, the rheology can be better characterized by the Power Law model for 70% to 80% quality foams.…”
Section: Foam Rheologymentioning
confidence: 99%